Pengaplikasian Prosedur Penggunaan Aviobridge Dalam Pelaksanaan Kerja Petugas Apron Movement Control Bandar Udara Supadio Pontianak - Romay Hamonangan Leo; Zenita Kurniasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Supadio Airport in Pontianak is a major air transport gateway in West Kalimantan, heavily reliant on aviobridge facilities to support passenger comfort and operational efficiency. However, the implementation of aviobridge operating procedures by Apron Movement Control (AMC) officers often faces challenges, such as procedural inconsistencies and technical obstacles. This study aims to analyze the compliance of AMC officers with standard operating procedures (SOP) for aviobridge usage and to identify the challenges encountered in its operation at Supadio Airport, Pontianak. This research employs a qualitative method with a descriptive approach. Data were collected through direct observation, in-depth interviews with AMC officers, and documentation studies related to SOP and aviobridge operational reports. Data analysis was conducted systematically to evaluate procedural implementation and identify inhibiting factors in AMC officers' performance. The results of the study showed that most AMC officers had implemented the SOP for operating the aviobridge well, but there were still some discrepancies, especially in the undocking process and coordination between units. The main obstacles faced included limited personnel in one shift, as well as technical problems with the aviobridge facilities, increasing training and coordination across units was needed to ensure optimal and safe aviobridge operations.